Implementasi kebijakan disiplin Pegawai Negeri Sipil di Kabupaten Minahasa - Lumingkewas, Elvis; Masengi, Evi Elvira; Supit, Brain Fransisco (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The aim of this research is to analyze the implementation of Civil Servant Discipline Policy in Minahasa Regency based on Government Regulation Number 94 of 2021 concerning Civil Servant Discipline. The research location is the Minahasa Regency Women's Empowerment and Child Protection Service. This research uses a qualitative method. The research results show that the work discipline of civil servants in the Minahasa Regency Women's Empowerment and Child Protection Service isn't yet ideal since there are still representatives who disregard the standards as per the appropriate arrangements in regards to limits on beginning and leaving available time. There are still employees who do not comprehend the Job Description in light of the Main Duties and Functions, they put off doing the work that is assigned to them, and their supervisors do not discipline them. Factors that ruin government employee discipline are administration endlessly factors from the actual workers as representative quality and mindset and absence of socialization of the execution of these administration guidelines.